2012
DOI: 10.1186/gm341
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomic profile as a means to distinguish stage of colorectal cancer

Abstract: BackgroundPresently, colorectal cancer (CRC) is staged preoperatively by radiographic tests, and postoperatively by pathological evaluation of available surgical specimens. However, present staging methods do not accurately identify occult metastases. This has a direct effect on clinical management. Early identification of metastases isolated to the liver may enable surgical resection, whereas more disseminated disease may be best treated with palliative chemotherapy.MethodsSera from 103 patients with colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 33 publications
2
103
0
3
Order By: Relevance
“…In this review, there was evidence that metabolite modulation was discernable at very early stages of GI cancer (30,46,52,(57)(58)(59). Several studies reported incremental metabolomic changes with invasive (41,43,58,59) and metastatic (46,70,71) progression. In addition, three studies in colorectal cancer that were excluded from the appraisal process owing to their design nonetheless demonstrated pertinent findings to metabolomic dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, there was evidence that metabolite modulation was discernable at very early stages of GI cancer (30,46,52,(57)(58)(59). Several studies reported incremental metabolomic changes with invasive (41,43,58,59) and metastatic (46,70,71) progression. In addition, three studies in colorectal cancer that were excluded from the appraisal process owing to their design nonetheless demonstrated pertinent findings to metabolomic dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Farshidfar et al performed a serum metabolomic profile to distinguish different stages of CRC patients among locoregional CRC, hepatic-specific metastases and extrahepatic metastases, which revealed that the metabolome changed markedly for the different stages [75]. Such metabolic changes were due to the difference in tumor biology as well as the site-specific host response to the tumor.…”
Section: Crc Metabolomics In Personalized Medicinementioning
confidence: 97%
“…Unterschiedliche Konzentrationen von Aminosäuren und Zuckern ließen auf einen gestörten Energiestoffwechsel schließen, d.h. Lipolyse, Krebszyklus und Aminosäure-Abbau. In einer Studie an 103 Patienten mit kolorektalem Adenokarzinom -davon 42 mit lokoregionärem Karzinom, 45 mit Lebermetastasen und 25 auch mit extrahepatischen Metastasen -konnte man außerdem eindeutig zwischen den verschiedenen Gruppen mittels NMR-Spektroskopie oder Gaschromatographie unterscheiden [76]. Diese Ergebnisse zeigen die universelle Einsetzbarkeit der NMR in der Krebsforschung, was zu neuen Erkenntnissen über gestörte Stoffwechselprozesse führt.…”
Section: Metabolomicsunclassified